ANALISIS PERAN AFFILIATED COMMISSIONER DALAM PENERAPAN GOOD CORPORATE GOVERNANCE PADA BISNIS KELUARGA - Sitardja, Meco; Lesmana, Iwan; Rumondang P, Safrida; Biantara, Dheny; Handayani, Sri (Lembaga Penerbitan Unversitas Esa Unggul, 2021)
This study aims to analyze the role of the board of commissioners in the implementation of Good Corporate Governance in family businesses. This study analyzed 18 research samples using purposive sampling method. In addition, this study uses an empirical normative approach. The results of the study indicate that the implementation of Good Corporate Governance in affiliated commissioner is quite good in the aspect of Responsiveness and Fairness. In further research, measurements of Good Corporate Governance can be added to several measurements of the ASEAN Governance Scorecard which include details of aspects that need to be carried out in supervision such as financial control, operational performance, risk management, internal control and performance appraisal of directors.